Testing measurements - PATERNOSTRO MARCELO; SLUIMAN HARM (2007)
Embodiments of the invention include a testing measurement which output a non-binary test result for one or more steps or processes performed during execution of a test of a subject. The non-binary test result, which may be output by a verification point or a test script, provides a developer with an improved gauge of the subject under test. In embodiments of the present invention, a test script or verification point will, rather than simply generate a "pass" or "fail" (i.e., "successful" or "unsuccessful") output, generate a non-boolean value providing data with improved correlation between the test output and the relative success of a test script. In some embodiments, each verification point or test script can be associated with a rule for determining the test output which can be easily modified. This aspect provides users with an ability to carefully develop and implement a test result rule which provides output which enhances test output data analysis.